Proceedings of the 8th ACM/SPEC on International Conference on Performance Engineering Companion 2017
DOI: 10.1145/3053600.3053647
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Performance of a Meta-modeling Architecture

Abstract: The Reflection architectural pattern is an elegant reusable solution to design software applications based on a metamodel that provides a self-representation of the types used in the domain model. This provides significant benefits in terms of adaptability, maintainability, self-awareness, and direct involvement of domain experts in the configuration stage. However, while virtuous in the perspective of objectoriented development, the meta-model adds a level of indirection that may result in poor performance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The relevance about studies about AOM can be confirmed by some recent works found in the literature that used directly or were based on this architectural style, such as for economy mechanics in digital games [3], model-driven architectures [4], [5], data evolution in digital ecosystems [6], meta-modeling architectures [7], and creating dynamic web services [8], [9]. But besides this architectural style is still applied, to the best of our knowledge, except for our previous work with Esfinge AOM Role Mapper [38]- [40], there are no other works in the last five years that focused on advances for the design of AOM architectures.…”
Section: Related Workmentioning
confidence: 86%
See 1 more Smart Citation
“…The relevance about studies about AOM can be confirmed by some recent works found in the literature that used directly or were based on this architectural style, such as for economy mechanics in digital games [3], model-driven architectures [4], [5], data evolution in digital ecosystems [6], meta-modeling architectures [7], and creating dynamic web services [8], [9]. But besides this architectural style is still applied, to the best of our knowledge, except for our previous work with Esfinge AOM Role Mapper [38]- [40], there are no other works in the last five years that focused on advances for the design of AOM architectures.…”
Section: Related Workmentioning
confidence: 86%
“…Several more recent studies employed AOM concepts for several applications and domains, such as for economy mechanics in digital games [3], model-driven architectures [4], [5], data evolution in digital ecosystems [6], meta-modeling architectures [7], and dynamic web services [8], [9]. That can be considered an evidence that this architectural style is still relevant and applied in recent works.…”
Section: Introductionmentioning
confidence: 99%